PERAN GURU BIMBINGAN DAN KONSELING DALAM MEREDUKSI PERILAKU MEROKOK PESERTA DIDIK SEKOLAH MENENGAH PERTAMA DI SURAKARTA - Muhammad Rizky Nur Prakoso, S.Pd, M.Pd (UNIVERSITAS SLAMET RIYADI, 2023)
Smoking behavior is a negative action that can damage health and cause environmental pollution. Apart from that, cigarettes are also a source of negative actions that can trigger juvenile delinquency and hinder students' developmental tasks. One of the roles of Guidance and Counseling (BK) teachers is to provide assistance and facilitate students who experience problems related to preventing smoking behavior and reducing/reducing this negative behavior. The research was carried out using quantitative descriptive methods. The data analysis technique uses content validity results using the Aiken formula. The research results showed that the role of guidance and counseling teachers and LKPD used in providing Classical Tutoring services was 87.76%, in the very good category. The conclusion of this research is that the role of guidance and counseling teachers in fulfilling the developmental tasks of adolescent students is as a companion or facilitator for students in fulfilling their rights and obligations, through preventative and curative/rehabilitation efforts carried out through individual/group counseling. Keywords: Role of Guidance and Counseling Teachers, Smoking Behavior, Individual Counseling